NATURAL DISASTER AS THE REASON TO WRITING OFF BANKING CREDIT IN INDONESIA - Siahaan, Rudy Haposan (Faculty of Law, Universitas Brawijaya, 2014)
Non-performing loans is a credit risk in the banking business. One of them is due to natural disasters and this is a force majeureÂ where the presence of unexpected events that occurred outside the fault of the debtor after entering into the agreement, these events preclude the debtor from fulfilling his achievements before debtor is declared to be negligent and therefore the debtor cannot be blamed and do not bear the risk for such events. Natural disasters are included in clause of force majeure. It must be explained the definition and criteria in the loan agreement in detail, as this brings the law result to writing off the debt (liabilities) to the creditor (Bank). The writing off bank credit as a result of natural disasters can be performed with the following reasons: a) The natural disaster was declared as a national disaster by the governments decision, b) Debtor bank including in the criteria that is directly affected by the disaster, and c) the obligation of reserving from the bank over loans given to debtor in the form of Loan Loss Provision (LLP). In addition to it, in practice, the non-legal factors settlement produce a new model law, therefore the writing off the non-performing due to natural disasters need strong legal basis within the framework of the legal system in the banking regulation in the form of legislation so that the force majeure clause of the Banking Credit Agreement has a binding force power.